Pengaruh Literasi Keuangan dan Gaya Hidup Konsumtif Terhadap Penggunaan Kredit Online Gen Z di Kabupaten Tasikmalaya - Ai nurmala; Aldy Agustian (MAMEN: Jurnal Manajemen, 2026)
This study investigates the influence of financial literacy and consumptive lifestyle on online credit usage decisions among Generation Z in Tasikmalaya Regency. Employing a quantitative research design with descriptive and verificative approaches, data were gathered from 105 respondents selected through purposive sampling. The collected data were analyzed using multiple linear regression techniques with the assistance of IBM SPSS Statistics version 31. The findings indicate that financial literacy has a positive and statistically significant partial effect on online credit usage decisions (p = 0.004 < 0.05; t = 2.952). Similarly, consumptive lifestyle also has a positive and significant effect, as evidenced by a significance value of 0.000 and a t-statistic of 8.162. Simultaneously, both independent variables significantly influence online credit usage decisions (p = 0.002). Based on the coefficient of determination (R²) value of 0.600, it can be concluded that financial literacy and consumptive lifestyle collectively explain 60.0% of the variance in online credit usage decisions, while the remaining 40.0% is influenced by other variables outside the scope of this study.